Prescription Patterns for the Use of Antihypertensive Drugs for Primary Prevention Among Patients With Hypertension in the United Kingdom. (27th August 2021) - Jiao, Tianze; Platt, Robert W; Douros, Antonios; Filion, Kristian B
Abstract: BACKGROUND: Several antihypertensive drugs are available for the primary prevention of cardiovascular disease (CVD). However, existing evidence on prescription patterns was primarily generated among patients at high CVD risk with short-term follow-up, and failed to capture impacts of time and patient characteristics. Our objective was therefore to describe longitudinal prescription patterns for antihypertensive drugs for the primary prevention of CVD among patients with arterial hypertension in the United Kingdom. METHODS: This population-based cohort study used data from the Clinical Practice Research Datalink, included 660, 545 patients with hypertension who initiated an antihypertensive drug between 1998 and 2018. Antihypertensive treatments were measured by drug class and described overall and in subgroups, focusing on first-line therapy (first antihypertensive drug(s) recorded after a diagnosis of hypertension) and second-line therapy (antihypertensive drug(s) prescribed as part of a treatment change following first-line therapy). RESULTS: Angiotensin-converting enzyme (ACE) inhibitors (29.0%), thiazide diuretics (22.1%), and calcium-channel blockers (CCBs) (21.0%) were the most prescribed first-line therapies. ACE inhibitors have been increasingly prescribed as first-line therapy since 2001. Men were more likely to be prescribed ACE inhibitors than women (43.5% vs. 32.1%; difference: 11.4%; 95% confidence interval [CI], 11.0%–11.8%), and Black patients were more likely to be prescribed CCBs than White patients (63.6% vs. 37.0%; difference: 26.6%; 95% CI, 24.8%–28.4%). CONCLUSIONS: Antihypertensive prescription patterns for the primary prevention of CVD among patients with hypertension are consistent with treatment guidelines that were in place during the study period, providing reassurance regarding the use of evidence-based prescribing. Graphical Abstract: